Development of E-Commerce for Selling Honey Bees in the COVID-19 Era - Indriani; Dar, Muhammad Halmi; Irmayanti, Irmayanti (Sinkron : jurnal dan penelitian teknik informatika, 2021)
During the Covid-19 pandemic, which has not yet ended, the business of selling honey is a type of business that is able to survive and even increase its market. The trend of selling honey in the era of the Covid-19 pandemic is quite stable and has the potential to be a good source of income because honey can be used as medicine and can increase the body's immunity. Fitorajo Bee Farm is a UMKM engaged in bee cultivation which is located in Pinang City, South Labuhanbatu Regency, North Sumatra Province with original honey bee products packaged in plastic bottle containers. The marketing system carried out by Fitorajo Bee Farm is carried out through word of mouth, Facebook social media, or through the WhatsApp application. Seeing the promising potential of the honey business in the Covid-19 pandemic era, and in order to reach a wider market, Fitorajo Bee Farm should improve and innovate by adopting e-commerce technology. Conventional marketing, which so far only reaches consumers on a limited scale, must be changed with a marketing system that can reach consumers from any corner. The purpose of this research is to build a marketing media for Fitorajo Bee Farm honey bees by implementing web-based e-commerce. The system development method used is the waterfall model, while the programming language used is PHP framework codeigniter with MySQL DBMS. The results showed that the codeigniter framework and MySQL DBMS can be applied to build e-commerce web-based honey bee marketing media.